Napoleon : a concise biography - Bell, David A. (David Avrom) (Oxford University Press, 2015)
This book provides a concise, accurate, and lively portrait of Napoleon Bonapartes character and career, situating him firmly in historical context. David Bell emphasizes the astonishing sense of human possibility--for both good and ill--that Napoleon represented. By his late twenties, Napoleon was already one of the greatest generals in European history. At thirty, he had become absolute master of Europes most powerful country. In his early forties, he ruled a European empire more powerful than any since Rome, fighting wars that changed the shape of the continent and brought death to millions. Then everything collapsed, leading him to spend his last years in miserable exile in the South Atlantic. Bell emphasizes the importance of the French Revolution in understanding Napoleons career. The revolution made possible the unprecedented concentration of political authority that Napoleon accrued, and his success in mobilizing human and material resources. Without the political changes brought about by the revolution, Napoleon could not have fought his wars. Without the wars, he could not have seized and held onto power. Though his virtual dictatorship betrayed the ideals of liberty and equality, his life and career were revolutionary.--